Studies on Frozen Storage Characteristics of Sole Fish Cynoglossus macrolepidolus - AGARWAL, ANIL (Fishery Technology, 2017)
Fresh sole fish (Cynoglossus macrolepidotus) was quick frozen at-40°C and stored at —18°C. Shelf life was evaluated by following biochemical, bacteriological and organoleptic changes occurring during storage. Rapid decrease was noted in the water extractable nitrogen and salt soluble nitrogen fractions. Samples of frozen sole fish remained in acceptable condition for 20 weeks.